The Effect of Workplace Violence on Depressive Symptoms and the Mediating Role of Psychological Capital in Chinese Township General Practitioners and Nurses: A Cross-Sectional Study - Tong, Chi (Psychiatry Investig, 2019)
OBJECTIVE: The most existing research has predominantly focused on city rather than township hospitals. This study aimed to explore depressive symptoms and its associated factors among general practitioners and nurses in Chinese township hospitals. METHODS: This cross-sectional study was carried out in Liaoning, China in 2016. 2,000 general practitioners and nurses in Chinese township hospitals were recruited and 1,736 of them became final subjects (effective response rate: 86.8%). Data on depressive symptoms, workplace violence (WPV), psychological capital (PsyCap), and demographic factors were collected through questionnaires. Hierarchical multiple regression was used to explore the factors related to depressive symptoms. Asymptotic and resampling strategies were applied to examine the potential mediating effect of PsyCap. RESULTS: The prevalence of depressive symptoms among the participants was 49.9%. Workplace violence was positively associated with depressive symptoms, whereas psychological capital and its components of hope, optimism and resilience were negatively associated with depressive symptoms. Psychological capital and its components of hope, optimism and resilience all played partial mediating roles between workplace violence and depressive symptoms. CONCLUSION: Nearly half of general practitioners and nurses surveyed suffered from depressive symptoms. Reduction of workplace violence and development of psychological capital can be targeted for interventions to combat depressive symptoms.